2011
DOI: 10.1080/08957959.2010.534989
|View full text |Cite
|
Sign up to set email alerts
|

Modification of polyamide-6 structure by combined methods of solid-phase extrusion

Abstract: Potentialities of new combined deformation schemes, including the solid-state extrusion through conical die (ED) and equal-channel multiple angle extrusion (ECMAE) implemented in different sequences to modify the structure and properties of semicrystalline polymers, have been studied for polyamide-6 (PA-6) as an example. It is shown that deformation by the ED-ECMAE scheme gives the best complex of physical and mechanical properties. A significal improvement of elastic and strength properties of PA-6 with a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…As the accumulated deformation ε increases, microhardness of both sections of polymer billet rises and Δ H declines. Behavior of Δ H differs from the traditional variant of solid‐phase extrusion, e.g., extrusion through a conic die when Δ H increases with ε increase, too 13. Absolute values of Δ H in the case solid state extrusion through a conic die exceed the values after ECMAE even at lower accumulated deformation.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…As the accumulated deformation ε increases, microhardness of both sections of polymer billet rises and Δ H declines. Behavior of Δ H differs from the traditional variant of solid‐phase extrusion, e.g., extrusion through a conic die when Δ H increases with ε increase, too 13. Absolute values of Δ H in the case solid state extrusion through a conic die exceed the values after ECMAE even at lower accumulated deformation.…”
Section: Resultsmentioning
confidence: 83%
“…A modified variant of ECAE is equal‐channel multiple‐angular extrusion (ECMAE) that implies presence of several zones of shear deformation within one device, in contrast to ECAE 2. That is why accumulation of high plastic deformation per one cycle takes place and at the same time, high homogeneity of deformation distribution through billet section is provided 10–13. A specific feature of ECMAE is possibility of realization of combination of different deformation routes during one cycle of the process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equal‐channel multiple angular extrusion (ECMAE) seems the most promising variant of ECAE because it provides change of space orientation of shear planes, intensity and value of accumulated strain for one pass . Using ECMAE makes possible formation of unique set of properties of semicrystalline polymers: high density and deformation‐strength characteristics with the minimal anisotropy .…”
Section: Introductionmentioning
confidence: 99%
“…[148][149][150][151][152][153][154][155][156] This research showed that by means of TE structural features and the ensuing properties of crystalline polymers can be modified significally. Application of TE to solid-state structural modification of polymers was reported in refs.…”
Section: Polymersmentioning
confidence: 99%